CD8+CD73+ T cells in the tumor microenvironment of head and neck cancer patients are linked to diminished T cell infiltration and activation in tumor tissue. Issue 12 (30th June 2020) - Panigrahi, Soumya; Bazdar, Douglas A.; Albakri, Marwah; Ferrari, Brian; Antonelli, Christopher J.; Freeman, Michael L.; Dubyak, George; Zender, Chad; Sieg, Scott F.
Abstract: Recent studies have implicated a role for adenosine‐dependent immunosuppression in head and neck tumor microenvironments. We describe expression of CD73, an enzyme critical to the generation of adenosine from extracellular AMP, in T cells and other cell types within human head and neck tumors. Flow cytometric analyses of tumor‐infiltrating cells indicate that CD3 + cells are the predominant source of CD73 among immune infiltrating cells and that CD73 expression, especially among CD8 + T cells, is inversely related to indices of T cell infiltration and T cell activation in the microenvironment of head and neck tumors. We provide evidence that CD73 expression on peripheral T cells and levels of soluble CD73 in circulation are correlated with CD73 expression on CD8 + T cells in tumors. Moreover, fluorescent microscopy studies reveal that CD8 + CD73 + cells are observed in close proximity to tumor cells as well as in surrounding tissue. In vitro studies with peripheral blood T cells indicate that anti‐CD3‐stimulation causes loss of CD73 expression, especially among cells that undergo proliferation and that exogenous AMP can impair T cell proliferation, while sustaining CD73 expression. These data suggest that CD8 + CD73 + T cells may be especially important mediators of immunosuppression in human head and neck cancer. Abstract : CD73 expression on T cells and other cell types can mediate immunosuppression by catabolizing extracellular AMP into adenosine, which in turn, impairs T cell activation and proliferation. We find that T cells represent the predominant hematopoietic cell type that expresses CD73 in the tumor microenvironment of head and neck cancers. The frequencies of CD8 + CD73 + T cells are inversely associated with T cell activation in the tumor tissue, suggesting that these cells may serve as an immune checkpoint that limits activation and expansion of tumor‐reactive T cells.